(untitled) (International Journal of Innovative Technologies in Economy, 2023)
This paper considers the main challenges of the economic policy and the changes in the structure of official reserves. The main risks of economic policy have been identified and certain interrelation of their distribution across countries has been established. The structure of official reserves and economic risks are examined using the example of six groups of countries. In particular, the G 7 countries, G 20 countries, G 20 countries without G 7 countries, 10 countries whose GDP is between 500 - 100 billion US dollars, 10 countries whose GDP is less than 100 billion US dollars and 10 countries whose GDP is between 50 - 10 billion US dollars. Some patterns in the distribution of economic risks and in the structure of official reserves have been established. It is concluded that it is a necessary review and improves the theoretical and methodological base and practice of placing Official Foreign Exchange Reserves.